2011
DOI: 10.1016/j.jacc.2011.05.011
|View full text |Cite
|
Sign up to set email alerts
|

A Genetic Variant of the Atrial Natriuretic Peptide Gene Is Associated With Cardiometabolic Protection in the General Community

Abstract: Objectives We sought to define the cardiometabolic phenotype associated with rs5068, a genetic variant of the atrial natriuretic peptide (ANP) gene. Background ANP and BNP play an important role in cardiorenal homeostasis but also exert metabolic actions. Methods We genotyped 1608 randomly selected residents from Olmsted County, Minnesota, USA. Subjects were well characterized. Results Genotype frequencies were: AA 89.9%, AG 9.7%, and GG 0.4%; all subsequent analyses were AA vs AG+GG. After adjustment fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
77
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(98 citation statements)
references
References 36 publications
13
77
1
1
Order By: Relevance
“…Following this study, we reported that the rs5068 allele was associated with increased NT-proANP levels, lower body mass index, C-reactive protein levels, BP, and waist circumference, with higher levels of high-density lipoprotein cholesterol (HDL-C) and a lower prevalence of MI and MetS in the general community of Olmsted County, MN. 26 We confirmed these findings in a general population study of Italians. 27 In addition, Jujic et al reported that 27,307 French non-diabetic individuals with the rs5068 minor allele had a lower incidence of diabetes within 14 years.…”
Section: Exogenous Treatment With Active Anp Molecular Formssupporting
confidence: 84%
“…Following this study, we reported that the rs5068 allele was associated with increased NT-proANP levels, lower body mass index, C-reactive protein levels, BP, and waist circumference, with higher levels of high-density lipoprotein cholesterol (HDL-C) and a lower prevalence of MI and MetS in the general community of Olmsted County, MN. 26 We confirmed these findings in a general population study of Italians. 27 In addition, Jujic et al reported that 27,307 French non-diabetic individuals with the rs5068 minor allele had a lower incidence of diabetes within 14 years.…”
Section: Exogenous Treatment With Active Anp Molecular Formssupporting
confidence: 84%
“…Further, human studies from NewtonCheh and coworkers have recently reported genetic variants of the ANP gene, which result in increased circulating ANP and are associated with lower BP and a reduced risk of hypertension [25, 26•]. Recent studies from Olmsted County, Minnesota, confirm the studies of Newton-Cheh demonstrating that the ANP genetic variant rs5058 is associated with reduced blood pressure [27]. Most importantly, this study by Cannone et al [27] also reported that rs5058 Fig.…”
Section: Atrial Natriuretic Peptide In Hypertensionsupporting
confidence: 59%
“…Recent studies from Olmsted County, Minnesota, confirm the studies of Newton-Cheh demonstrating that the ANP genetic variant rs5058 is associated with reduced blood pressure [27]. Most importantly, this study by Cannone et al [27] also reported that rs5058 Fig. 1 Biological actions and the metabolic and enzymatic clearance of atrial natriuretic peptide (ANP).…”
Section: Atrial Natriuretic Peptide In Hypertensionmentioning
confidence: 53%
“…In the same cohort, the variant rs5068 within the ANP gene, which results in enhanced plasma ANP levels, was associated with a 12% reduced adjusted-risk of incident diabetes (61). Furthermore, other studies have reported that the rs5068 variant is associated with lower BMI, waist circumference, and prevalence of obesity and MetS (62,63).…”
Section: Diabetesmentioning
confidence: 77%